Efficacy of Glargine Insulin Compared with Neutral Protamine Hagedorn Insulin in Patients with Type 2 Diabetes not Controlled with Oral Hypoglycemics: A Cohort Study - Ebtihal Bilal; Shamaila Burney; Muhammad Usman Sajid; Nabila Shaukat; Muhammad Farooq (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the efficacy of Glargine Insulin with Neutral Protamine Hagedorn (NPH) Insulin in patients with uncontrolled type 2 diabetes with oral hypoglycemic.